A New Model for Water Retention and Hydraulic Conductivity Curves of Deformable Unsaturated Soils - Zhenxing Chang; Chao Zhou (Water Resources Research)
Abstract The water retention and hydraulic conductivity curves of unsaturated soils are important parameters for seepage analysis. Experimental results in the literature generally show that with increasing density, the air‐entry value and adsorption/desorption rate of the water retention curve increase and the relative hydraulic conductivity (kr) at a given degree of saturation changes. The above phenomena, except the density‐dependency of air‐entry value, have not been considered in existing models. This study aims to address these problems by developing new hydraulic models based on experimental evidence from microscopic analysis. First of all, a new equation was proposed to model the evolution of pore size distribution with soil density. For a given pore, the ratio of its initial to final sizes is higher when the initial size is larger and when there is a greater increase in density. Based on this equation, a new and simple water retention equation was derived to predict the increase in air‐entry value (resulting from the reduction in pore size) and the adsorption/desorption rate (due to a more uniform pore size distribution) as density increases. Then, a new equation for kr was developed by incorporating the evolution of pore size distribution and tortuosity upon soil deformation, and therefore it can capture the changes of kr. To validate the above equations, test data from several soils with distinct properties were used. The measured and calculated results are well‐matched.